Mobility and Biography - Panter, Sarah (Jahrbuch für Europäische Geschichte / European History Yearbook, 2015)
The subject of transnational lives has only recently gained importance in historical research. With its transnational approach to "mobility and biography," this volume brings together research on aspects of mobility and biography across different times and spaces to open up new interdisciplinary perspectives. Networks, movements and the capacity to become socially or spatially mobile in and across Europe are not only analysed as structural factors, but rather seen as connected to concrete practices of mobility among different groups in the spheres of business, politics and the arts: from Jewish merchants via legal and financial advisors all the way to musicians.